Peran Moderasi Komite Audit pada Pengaruh Tenur, Rotasi Mandatori dan Rotasi Voluntari terhadap Kualitas Audit - Awaluddin, Awaluddin; Ardianto, Ardianto; Fanani, Zaenal (E-Jurnal Akuntansi, 2022)
The debate about the enactment of the auditor partner rotation and audit tenure restriction and their effect on audit quality still leave questions, because several studies have found inconsistent results. This study aims to provide empirical evidence of the moderating effect of the audit committee on the relationship of audit tenure and auditor partner rotation on audit quality, which may have caused the inconsistency of several previous studies. This study uses data from manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017 to 2019 using moderated regression analysis (MRA). The results show that the audit committee has an important role in influencing audit quality because it significantly moderates the effect of audit tenure and mandatory rotation on audit quality. Those moderating effects tend to reduce audit quality, those effects are related to the role of the audit committee in monitoring the audit process. Keywords: Audit Committee; Tenure; Voluntary Rotation; Mandatory Rotation.